Making Scientific Papers Training for Lecturers - Aslichah Aslichah; Betty Rahayu; Wina Nurhayati; I Nyoman Tri Sutaguna; Anang Rohmad Jatmiko (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Lecturers have a big influence on the standard of education in the country. A lecturer should enhance their skills outside of the classroom with the intention of improving themselves. The writing of scientific papers is a talent that educators can develop by taking part in writing workshops. This article's goal is to look into the beliefs and actions of the professors at Darul Ulum University. The lecturers are more receptive and excited about leading this scientific writing workshop as a result of this training. In addition, 25 of the 46 academics were able to proceed with further in-depth research since they had developed a good writing structure.